New records of Psocoptera from Egypt - Georgiev, Dilian (Journal of BioScience and Biotechnology, 2021)
A total of six species of Psocoptera were collected from Egypt (Cairo city – 5 species, Hurghada city – 1 species). Three of them were new records for Egypt.